Pedagogical Possibilities of Using Educational Tasks in the Development of Students' Speaking Competence Based on Interdisciplinarity - Uteuliyeva Mexriban Ibraimovna (Web of Journals Publishing, 2023)
This article explores the pedagogical possibilities of using educational tasks to enhance students' speaking competence through an interdisciplinary approach. The study investigates how incorporating various subjects and knowledge domains can contribute to the development of students' speaking skills. The research highlights the importance of interdisciplinarity in fostering a holistic learning experience, emphasizing the integration of language learning with other academic disciplines. The article also discusses practical implications and strategies for implementing educational tasks that promote students' speaking competence through an interdisciplinary lens.
Keywords: pedagogy, educational tasks, speaking competence, interdisciplinarity, student development.